Leptin Mediates In Vivo Neutrophil Migration: Involvement of Tumor Necrosis Factor-Alpha and CXCL1 - Souza-Almeida, Glaucia; D’Avila, Heloisa; Almeida, Patricia E.; Luna-Gomes, Tatiana; Liechocki, Sally; Walzog, Barbara; Hepper, Ingrid; Castro-Faria-Neto, Hugo Caire; Bozza, Patricia T.; Bandeira-Melo, Christianne; Maya-Monteiro, Clarissa M. (Frontiers in Immunology, 2018)
Leptin directly activates macrophages and lymphocytes, but the role of leptin in neutrophil activation and migration is still controversial. Here we investigate the in vivo mechanisms of neutrophil migration induced by leptin. Intraperitoneal injection of leptin (1 mg/Kg) induces a time- and concentration-dependent neutrophil influx. We did not observe enhancement of lipid bodies/droplets in neutrophils, after leptin treatment, as we had observed previously in peritoneal macrophages. The participation of LTB4 in neutrophil recruitment triggered by leptin was investigated using different strategies. Leptin-induced neutrophil recruitment occurs both in the absence of 5-lipoxygenase activity in 5-LO-/- mice, and after administration of either 5-LO inhibitor (Zileuton) or the LTB4 receptor antagonist (U-75302). Moreover, no direct induction of LTB4 by leptin could be observed. Neutrophil influx could not be prevented by the mTOR inhibitor, rapamycin, contrasting with the leptin-induced signaling for lipid body formation in macrophage, that is mTOR dependent. Leptin administration led to TNF production by peritoneal cells both in vivo and in vitro. In addition, neutrophil recruitment was inhibited in TNFRI-/- mice, indicating a role for TNF in leptin-induced neutrophil recruitment to the peritoneal cavity. Leptin-induced neutrophil influx was PI3K dependent, as it was absent in PI3K-/- mice. Accordingly, leptin induced peritoneal cells to produce CXCL1, both in vivo and in vitro, and the neutrophil influx was ablated after using an antibody against CXCL1. Our results establish TNF/TNFRI and CXCL1 dependent signaling as important pathways for leptin induced neutrophil migration in vivo.